The Importance-Performance Map Analysis of Performance-Based Pay Management and Procedural Justice in Malaysian Government-Linked Company - Abd Razak, Mohd Ridwan; Ali, Enah; Kolandan, Subramaniam (International Journal of Economics, Management and Accounting, 2026)
Performance-based pay management (PBPM) is a strategic approach in human resource management to achieve organizational sustainability in a competitive business landscape. This research aimed at assessing the relationship between PBPM’s components (i.e. communication, participation, and performance evaluation) and procedural justice, and to evaluate the importance and performance of each element using Importance-Performance Map Analysis (IPMA). A cross-sectional approach was used to collect usable data through questionnaire survey on 400 employees from Malaysian Government-Linked Companies. SmartPLS software version 4 was used to analyze the survey data. Consistent PLS-SEM Bootstrapping analysis indicates three important findings. First, the relationship between communication and procedural justice was significant. Second, the relationship between participation and procedural justice was non-significant. Lastly, the relationship between performance appraisal and procedural justice was significant. Further, IPMA analysis indicates that performance evaluation is the most critical and well-executed component, followed by communication, and participation. This study provides empirical evidence on the importance of effective communication, participation, and systematic performance evaluation in managing performance-based pay to enhance employee perception of procedural justice. The findings of this study contribute significant insights to the theory, research methodology, practitioner, and social aspects of Performance-based Pay Management (PBPM).